Identification of multiple binding sites for the THAP domain of the Galileo transposase in the long terminal inverted-repeats - Marzo, Mar; Liu, Danxu; Ruiz, Alfredo; Chalmers, Ronald (Elsevier, 2013)
Galileo is a DNA transposon responsible for the generation of several chromosomal inversions in Drosophila. In contrast to other members of the P-element superfamily, it has unusually long terminal inverted-repeats (TIRs) that resemble those of Foldback elements. To investigate the function of the long TIRs we derived consensus and ancestral sequences for the Galileo transposase in three species of Drosophilids. Following gene synthesis, we expressed and purified their constituent THAP domains and tested their binding activity towards the respective Galileo TIRs. DNase I footprinting located the most proximal DNA binding site about 70 bp from the transposon end. Using this sequence we identified further binding sites in the tandem repeats that are found within the long TIRs. This suggests that the synaptic complex between Galileo ends may be a complicated structure containing higher-order multimers of the transposase. We also attempted to reconstitute Galileo transposition in Drosophila embryos but no events were detected. Thus, although the limited numbers of Galileo copies in each genome were sufficient to provide functional consensus sequences for the THAP domains, they do not specify a fully active transposase. Since the THAP recognition sequence is short, and will occur many times in a large genome, it seems likely that the multiple binding sites within the long, internally repetitive, TIRs of Galileo and other Foldback-like elements may provide the transposase with its binding specificity.